The Effect of Different Irrigation Interval on Tuber Yield and Quality of Potato (Solanum tuberosum L.) - Salih, Salah Abdulla; Abdulrahman, Farhan Ahmad; Mahmood, Yonis Abdulla (Kurdistan Journal of Applied Research, 2018)
Gaining high yield of potato is very crucial for farmer and quality also has a great impact on their production. Beside the quality and yield using the amount of irrigation also important to reduce water lose. The tuber yield and quality of potato (Solanum tuberosum L.) is impacted by irrigated water. This study was carried out in two respectively season (2017 and 2018) in Halabja province of Kurdistan regional of Iraq to evaluate the impact of irrigation interval on quality and tuber yield in potato cultivars. In this study there are four irrigation intervals (3,5,7 and 9 days) used by furrow irrigation method which subjected in complete randomized design (CRD) with three replications. The potato tuber production in 3 day interval showed highest percentage also protein and starch content was recorded highest in both year of cultivation, but the abscisic acid was affected by more irrigation which in 3 day interval irrigation the rate was less than other. Also in 5 day interval irrigation the rate was acceptable because there is no significant difference in terms of tuber yield, protein and starch content if compare with 3 day interval irrigation in particular for those area faced restricted in using water irrigation.